Supply chain resilience in the colombian defense sector before and during the COVID-19 pandemic : a comparative study (2023)
Unforeseen events can significantly affect organizations’ supply chains and disrupt their continuous flow. Therefore, organizations need to develop a response capability that allows them to minimize the negative effect of such events and quickly recover from them, also known as resilience. This research performs a comparative analysis of the influence that risk, vulnerability, and adaptability have on the resilience capability of supply chains in Colombian defense sector organizations before and during the coronavirus outbreak. Based on a literature review, a survey was designed and applied online to collect data from respondents related to the activities of the Colombian Air Force supply chain. For the first wave, data was collected between December 2019 and January 2020. Data for the second wave was collected in August 2020. Results suggest that identifying and managing risks positively impact reducing vulnerability and increasing adaptability. Moreover, by decreasing exposure and improving adaptability, the organization positively influences supply chain resilience capability. The results also indicate that the pandemic positively affected risk and vulnerability awareness. The identification of vulnerabilities had a positive impact on the resilience capacity during the Corona Virus outbreak. This research provides relevant information for the Colombian government on developing public policies and mechanisms of service and support for defense sector organizations to strengthen their resilience capability. Likewise, the study offers valuable information to those organizations interested in improving their resilience capability and that of the sector in which they are involved.